Failing to deliver: why pregnancy is not a disease - Rezkalla, Paul (Journal of medical ethics, 2025)
In their article ‘Is Pregnancy a Disease? A Normative Approach’, Anna Smajdor and Joona Räsänen contend that, on several of the most prominent accounts of disease, pregnancy should be considered a disease. More specifically, of the five accounts they discuss, each renders pregnancy a disease or suffers serious conceptual problems otherwise. They take issue specifically with the dysfunction account of disease and argue that it suffers several theoretical difficulties. In this response, we focus on defending the dysfunction account against their main objections and show why a version of the dysfunction account is viable on account of the indispensability of normativity in biology and medicine. After disarming their main objections to the dysfunction account, we briefly respond to their treatment of the normality of pregnancy and then draw a distinction between adverse symptoms and underlying causes to show why even though pregnancy may have ‘disease-like’ features, it is not a disease.